The Relationship of Self-confidence with Dribbling Skill: A Correlation Study on Young Football Players - Razali Razali; Zulfikar Zulfikar; Karimuddin Karimuddin; Myra Akbari (Proceedings of AICS - Social Sciences, 2021)
Dribbling is one type of skill that must be possessed by a football player. One indicator of the quality of a good football player is being able to show good dribbling skills when playing football. Based on theoretical studies, to be able to dribble well, a football player must have a good mentality; one of the mentalities needed when dribbling is to have good self-confidence. The purpose of this study was to determine the relationship between variables, namely self-confidence and dribbling skills. This research approach is quantitative with the type of correlational research. The population in this study was young players from the